Strategies for Combating Sexual Harassment in Islamic Higher Education - Istiadah Istiadah; Aprilia Mega Rosdiana; Laily Fitriani; Sulalah Sulalah (Universitas Islam Negeri Jakarta, 2020)
Recent series of widely-published sexual harassment at Maulana Malik Ibrahim State Islamic University (UIN) Malang arise a question on how this Islamic campus handles the situation and promotes institutional change. This research examines sexual harassment and the way the UIN deals with it. It employs participatory action research to make it possible for researchers and stakeholders to work together to find out the strategies to prevent sexual harassment. This research obtains three strategies to prevent and combat sexual harassment including comprehensive planning strategies, infrastructure development, and building key partnerships. These partnerships include revitalizing the functions of the academic counselor, conducting campaigns against sexual harassment, building a positive-content website, integrating sexual education with the learning curriculum, and keeping relationships with the surrounding sub-district heads for the students’ control. Further research is supposed to examine and reflect on the result of the respected actions to find out the most suitable prevention, intervention, and policy protocols for Islamic higher education. AbstrakSerangkaian pelecehan seksual yang dipublikasikan secara luas di Universitas Islam Negeri (UIN) Maulana Malik Ibrahim Malang baru-baru ini menimbulkan pertanyaan tentang bagaimana kampus Islam ini menangani situasi dan mendorong perubahan kelembagaan. Penelitian ini mengkaji pelecehan seksual dan cara UIN menanganinya. Penelitian ini menggunakan penelitian aksi partisipatif agar peneliti dan pemangku kepentingan dapat bekerja sama untuk mengetahui strategi pencegahan pelecehan seksual. Penelitian ini memperoleh tiga strategi untuk mencegah dan memberantas pelecehan seksual antara lain strategi perencanaan yang komprehensif, pembangunan infrastruktur, dan membangun kemitraan kunci. Kemitraan tersebut mencakup revitalisasi fungsi konselor akademik, kampanye anti pelecehan seksual, pembuatan situs web yang berisi konten positif, pemaduan pendidikan seksual dengan kurikulum pembelajaran, dan menjaga hubungan dengan camat di sekitarnya untuk dikontrol siswa. Penelitian lebih lanjut diharapkan untuk memeriksa dan merefleksikan hasil dari tindakan yang dihormati untuk menemukan protokol pencegahan, intervensi, dan kebijakan yang paling sesuai untuk perguruan tinggi Islam.